PENINGKATAN PENGETAHUAN ORANG TUA TENTANG ANEMIA PADA ANAK DENGAN MEDIA APLIKASI ANEMIA ANAK - Yuliantisari Retnaningsih; Nur Djanah (Bajang Institute, 2024)
Health problems where a person experiences a lack of red blood cells in the body, known as anemia, are known to have a major impact on physical health, social and economic well-being. According to global data, the prevalence of anemia is 47% in children under 5 years of age. Maternal knowledge plays a very important role in preventing anemia. The higher the mother's knowledge, the better her anemia prevention behavior will be. The aim of community service activities is to increase mothers' knowledge about anemia in children. This community service activity was carried out in the Segoroyoso Pleret Bantul Village Hall and was attended by 40 mothers with toddlers. The method used was lectures and questions and answers using children's anemia application tools as an effort to convey information about anemia in children. The results of the activity showed an average pre-test score of 55 and an average post-test score of 93. The conclusion of this community service activity was an increase in mothers' knowledge about children's anemia after being given lectures, questions and answers using children's anemia application tools, so that mothers -mothers understand more about children's anemia